Respuesta :

snog

Answer:

see below

Step-by-step explanation:

Multiplying the equation by 2x - 2 on both sides to cancel out the denominator gives us (x - 1)(x + 2)(x - 3)(x + 7)(x - 5) = 0. Using Zero Product Property and setting each factor to 0, we get:

x - 1 = 0 or x + 2 = 0 or x - 3 = 0 or x + 7 = 0 or x -  5 = 0

x = 1, x = -2, x = 3, x = -7, x = 5

Unfortunately, x cannot be 1 as the numerator would become 0 and then the expression on the left side would become undefined so the final answer is x = -2, x = 3, x = 7, x = 5.